Pathfinding and Connections in the Life of Small Reformed Communities in Budapest. The Contexts of the 1967 YMCA Trial - Réka KISS (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
In July 1967, the communist political police arrested five members of Keresztyén Ifjúsági Egyesület (the Hungarian equivalent of the YMCA), which had been dissolved in 1950, on charges of conspiracy against the state. Among those arrested were pastors, elders, and a former deacon. The trial is considered to be the last politically motivated trial against the Reformed Church and the most significant of all state security actions against the Reformed in Hungary. In order to understand the background of the trial and the changing considerations of church policy and state security surrounding it, it is necessary to look at how the image and political approach of the decisive actors of church policy had evolved by the 1960s. On the other hand, the documents produced by the party-state can be examined not only from the perspective of power but also from that of communities in action: what were the individual and collective strategies for active Christianity in the first decades of the Kádár regime? What were the individual and collective aspirations, adaptation techniques, and patterns of value transmission that can be discerned among different groups, congregations, youth communities, and their leaders in Reformed Christianity? Which forms of church or religious behaviours were considered dangerous by the party-state, and how did it set forth for the church policy enforcement bodies the activities it considered to be within the category of church or religious resistance and opposition?